Situation Report: Poland, 12 March 1964 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. CC Plenum to Discuss Party Congress Church News Kekkonen Leaves Poland Jerzy Morawski to Geneva? Polish-West German Trade Commission Meets Poland Buys Grain in Sweden Algerian and Turkish Trade Delegation in Warsaw